Entre o Mosteiro de São Bento e a cidade: o canto gregoriano e o acústico contemporâneo da Cidade de São Paulo - Oliveira, Vinicius Morais de (2014)
The central theme of this dissertation is to historicize the present time, the domestic soundscape of the Monastery of São Bento, the medieval remnants contained in its architecture and in its musical production, beside all dichotomous, accelerated and noisy loudness of its surroundings‟ urban sounds. Both spaces have their sonorous territories‟ identities. In view of the prominence that the sound production‟s study of societies is creating new possibilities for the current historiography, the research issue also sought to provide subsidies to the historical investigation of the music writing reading rules through gregorian chant and the whole complex set of nomenclatures derived from musicological analysis. It also proposes a restructuring in the ocular mechanism hierarchy in equilibrium with the conscious listening of sounds, promoting new cognitive models of our sensitive capacities. Thus, the main documentary sources used were sound sources, a small photographic collection and oral reports from people who passed by in both spaces